THE IMPORTANCE OF FOLK PEDAGOGY IN TEACHING STUDENTS CRITICAL THINKING - Babasheva, G.B. (SCIENCE and SOCIETY, 2026)
This article provides a scientific and theoretical analysis of the pedagogical, psychological, and methodological significance of folk pedagogy in the process of developing students’ critical thinking competence. The study substantiates the possibilities of fostering learners’ independent, analytical, and critical thinking through the use of key sources of folk pedagogy – proverbs and sayings, fairy tales, epics, riddles, legends, as well as national traditions – within the educational process. Furthermore, the paper highlights ways to enhance the effectiveness of education by integrating folk pedagogy with modern pedagogical technologies.
Keywords: critical thinking; folk pedagogy; educational process; national values; independent thinking; pedagogical integration